Finite element modelling of the structural response of roof to wall framing connections in timber-framed houses. (1st March 2017) - Satheeskumar, N.; Henderson, D.J.; Ginger, J.D.; Wang, C.H.
Highlights: Structural response of roof to wall connections to loading. Finite element model development and validation of the roof to wall connections. Variations in uplift capacity with construction defects and oblique loads. Abstract: The structural response and performance of connections are particularly important to assess the vulnerability of timber-framed structures to windstorms. Finite element (FE) analysis using ABAQUS (6.12-3) software is used in this study to determine the structural response and uplift capacities of typical roof to wall connections. Results (i.e. force-displacement relationship and failure modes) of the FE model were compared with experimental tests and the model validated from the test results. The FE model accounts for large deformation as well as the contact between nail and timber through the elastic and post-elastic phases up to failure. The dominant failure modes observed are nails and framing anchor bending, and nail pull out. The FE model produced structural responses and uplift capacities that generally agree with the experimental results. Construction defects (i.e. missing nails) in a roof to wall connection influences the design uplift capacity. Nails located near the centre line of the loading action in a triple grip connection (i.e. common roof to wall connection used in the timber-framed house of Australia) significantly affect the stiffness of this connection. The response of these nails dominated the uplift capacity and failure types of triple grip connection to loading. Missing a nail in both truss and top-plate in the triple grip connection reduces the design uplift capacity by 40% of the "Ideal" triple grip connections. The roof to wall connection subjected to a combination of lateral and vertical loads, gave a connection capacity of about 55% less than the uplift capacity specified in the standards. The outcome of this study shows that the FE model analysis methods used in this study can be used to assess and predict the structural response and design uplift capacity of the roof to wall connection.